Pravastatin modulates liver bile acid and cholesterol homeostasis in rats with chronic cholestasis - Kolouchova, Gabriela; Brcakova, Eva; Hirsova, Petra; Sispera, Ludek; Tomsik, Pavel; Cermanova, Jolana; Hyspler, Radek; Slanarova, Martina; Fuksa, Leos; Lotkova, Halka; Micuda, Stanislav (Journal of gastroenterology and hepatology, 2011)
BACKGROUND AND AIM: The administration of pravastatin to patients with cholestatic liver disease has suggested the potential of the drug with regard to reducing raised plasma cholesterol and bile acid levels. Information about the mechanisms associated with this effect is lacking. Thus, the aim of the present study is to evaluate pravastatin effects on the liver bile acid and cholesterol homeostasis in healthy and cholestatic rats. METHODS: Control sham-operated and reversibly bile duct-obstructed (BDO) rats were treated with pravastatin (1 or 5 mg/kg) or the vehicle alone for 7 days after surgery. RESULTS: Lower doses of pravastatin reduced bile acid plasma concentrations in cholestatic animals. The effect was associated with reduced liver mRNA expression of Cyp7a1, Cyp8b1, Mrp2, Ugt1a1 and the increased expression of Bsep. In addition, BDO-induced increase in the liver content of cholesterol was normalized by pravastatin. The change was accompanied by the reduced liver expression of Hmg-CoA reductase, LDL receptor, and Acat2, and induced the expression of Abca1 and Mdr2. These changes corresponded with the upregulation of nuclear receptors LXRα and PPARα, and the downregulation of FXR, CAR, SREBP-2 and HNF1α. High doses of pravastatin lacked any positive effects on bile acids and cholesterol homeostasis, and blocked bile formation through the reduction of the biliary excretion of bile acids. CONCLUSIONS: Pravastatin rendered a positive reduction in BDO-induced increases in plasma bile acid concentrations and cholesterol liver content, mainly through the transcriptionally-mediated downregulation of genes involved in the synthesis of these compounds in the liver.
Keywords: játra; membránové transportní proteiny; Cholesterol; statiny; Bile Acids and Salts; messenger RNA; cholesterol; permeabilita; žlučové kyseliny a soli; regulace genové exprese enzymů; Transcription Factors; Permeability; modely nemocí na zvířatech; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Chronic Disease; Pravastatin; krysa rodu Rattus; Membrane Transport Proteins; zvířata; potkani Wistar; časové faktory; Cholestasis; RNA, Messenger; Liver; Rats, Wistar; homeostáza; Male; chronická nemoc; Homeostasis; Rats; Gene Expression Regulation, Enzymologic; transkripční faktory; Animals; mužské pohlaví; Disease Models, Animal; Time Factors; cholestáza; pravastatin